1986
DOI: 10.1111/j.1365-2028.1986.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five natural soil licks, Benoue National Park, Cameroon, West Africa

Abstract: Summary Use of natural licks by wild animals during the dry season in Benoue National Park, Cameroon, prompted a closer examination of lick soils. The emphasis in the study was to isolate the factor(s) attracting wild animals to licks. Mechanical and chemical analysis determined the variables (%) water content, (%) organic matter, pH, electrical conductivity, extractable calcium, magnesium, potassium, and sodium, and available phosphorus and sulphate‐sulphur. A stepwise multiple regression analysis was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies showed that sodium is the main element sought by animals visiting licks (Holdo et al . 2002, Moe 1993, Stark 1986, Tankersley & Gasaway 1983, Tracy & McNaughton 1995), but other elements found in elevated concentration in lick soils are calcium, magnesium and potassium (Emmons & Stark 1979, Jones & Hanson 1985, Klaus 1998, Montenegro 2004). Montenegro (2004) analysed tapir diet in northern Peru and showed that sodium requirements cannot be met through the browse and fruits tapirs eat.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that sodium is the main element sought by animals visiting licks (Holdo et al . 2002, Moe 1993, Stark 1986, Tankersley & Gasaway 1983, Tracy & McNaughton 1995), but other elements found in elevated concentration in lick soils are calcium, magnesium and potassium (Emmons & Stark 1979, Jones & Hanson 1985, Klaus 1998, Montenegro 2004). Montenegro (2004) analysed tapir diet in northern Peru and showed that sodium requirements cannot be met through the browse and fruits tapirs eat.…”
Section: Discussionmentioning
confidence: 99%